2018
DOI: 10.1002/wps.20527
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in 7‐year‐old children with familial high risk of developing schizophrenia spectrum psychosis or bipolar disorder – The Danish High Risk and Resilience Study ‐ VIA 7, a population‐based cohort study

Abstract: This study aimed to compare the psychopathological profiles of children at familial high risk of schizophrenia spectrum psychosis (FHR-SZ) or bipolar disorder (FHR-BP) with population-based controls. We used Danish nationwide registers to retrieve a cohort of 522 seven-year-old children of parents with schizophrenia spectrum psychosis (N=202), bipolar disorder (N=120) or none of these disorders (N=200). Psychopathology was assessed by reports from multiple informants, including children, parents and teachers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 44 publications
9
59
0
Order By: Relevance
“…Our teacher-report measures confirmed that neuropsychiatric impairments were present in multiple settings, indicating pervasiveness. Our findings of broad ranging impairments is consistent with studies of common polygenic risk 37 and familial risk 38,39 of psychiatric disorder, that find that genetic risk is associated with disrupted childhood neurodevelopment across several domains. Psychiatric disorder was present in control siblings at rates in line with previous population studies that have used the same instruments as in the current study 40,41 as well as with previous studies that have compared ND-CNV carriers to controls 42,43 .…”
Section: Discussionsupporting
confidence: 90%
“…Our teacher-report measures confirmed that neuropsychiatric impairments were present in multiple settings, indicating pervasiveness. Our findings of broad ranging impairments is consistent with studies of common polygenic risk 37 and familial risk 38,39 of psychiatric disorder, that find that genetic risk is associated with disrupted childhood neurodevelopment across several domains. Psychiatric disorder was present in control siblings at rates in line with previous population studies that have used the same instruments as in the current study 40,41 as well as with previous studies that have compared ND-CNV carriers to controls 42,43 .…”
Section: Discussionsupporting
confidence: 90%
“…The negative association of PTSD was not mediated through co-morbidity with depression, psychosis or bipolar disorder. School performance in children of parents with PTSD was lower than in children of parents with major psychiatric disorders such as psychosis and bipolar disease, which was quite surprising given the severity of these conditions and the strong association between such parental psychopathology and children's adverse outcomes [9,10,[21][22][23]. Parental PTSD has previously been shown to have adverse effects on children's psychological distress and behavioural problems [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several published studies, narrative reviews and meta-analyses informing the prevalence and age of onset of psychopathology in children of variably identified and diagnosed samples of bipolar parents published over the last few decades (Duffy et al 2011(Duffy et al , 2017bDelBello and Geller 2001;Lau et al 2018;Lapalme et al 1997;Ellersgaard et al 2018). Several of these studies have repeatedly assessed high-risk children through the peak period of risk from childhood into early adulthood (Mesman et al 2013;Duffy et al 2018b;Axelson et al 2015;Preisig et al 2016;Egeland et al 2012).…”
Section: Longitudinal High-risk Studiesmentioning
confidence: 99%
“…Given that the BIOS sample were younger this might have impacted the rate of co-morbidity and age of onset of bipolar disorder. However reducing this possibility, the Danish High Risk and Resilience Study-VIA 7, a nationwide population-based cohort study of 522 7-year-old (age range 6.9-8.4 years) high-risk children (Ellersgaard et al 2018), reported a higher prevalence of anxiety disorders, stress and adjustment disorders compared with controls and no cases of prepubertal bipolar disorder. Another cross-national study of mania in adults reported that UK psychiatrists were less likely to endorse symptoms on the Young Mania Scale than were clinicians from the US or India (Mackin et al 2006).…”
Section: Cross-national Differencesmentioning
confidence: 99%